An integrated approach for planning a long-term care network with uncertainty, strategic policy and equity considerations - Cardoso-Grilo, T.; Oliveira, M. D.; Barbosa-Póvoa, A.; Nickel, S. (European Journal of Operational Research, 2015)
Considering key uncertainties and health policy options in the reorganization of a long-term care (LTC) network is crucial. This study proposes a stochastic mixed integer linear programming model for planning the delivery of LTC services within a network of care where such aspects are modeled in an integrated manner. The model assists health care planners on how to plan the delivery of the entire range of LTC services – institutional, home-based and ambulatory services – when the main policy objective is the minimization of expected costs and while respecting satisficing levels of equity. These equity levels are modeled as constraints, ensuring the attainment of equity of access, equity of utilization, socioeconomic equity and geographical equity. The proposed model provides planners with key information on: when and where to locate services and with which capacity, how to distribute this capacity across services and patient groups, and which changes to the network of care are needed over time. Model outputs take into account the uncertainty surrounding LTC demand, and consider strategic health policy options adopted by governments. The applicability of the model is demonstrated through the resolution of a case study in the Great Lisbon region in Portugal with estimates on the equity-cost trade-off for several equity dimensions being provided.